2021
DOI: 10.1186/s12935-020-01710-0
|View full text |Cite
|
Sign up to set email alerts
|

XPF expression and its relationship with the risk and prognosis of colorectal cancer

Abstract: Background XPF (xeroderma pigmentosum complementation group F) is a key factor contributing to DNA damage excision of nucleotide excision repair pathway. The relationship between XPF expression and the risk and prognosis of colorectal cancer (CRC) is unclear. Methods In this experiment, a total of 824 cases of colorectal tissue were collected. XPF protein expression was detected by immunohistochemical staining. We conducted a Mann–Whitney U test in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…As the main member of the second defense line in the antioxidant system, GST can catalyze covalent conjugation reactions between glutathione and toxic electrophilic and hydrophobic substances to produce substances with anti-lipid peroxidation effects. In addition, it can react with some exogenous or endogenous metabolites, such as cholic acid and hormones, which are insoluble in water, to generate some water-soluble compounds, and then they are excreted from the body, thereby protecting brain tissue from antioxidant damage and reducing cellular damage by free radicals and toxic substances [ 39 ]. The results showed that appropriate concentrations of EPA, ALA, or DHA could improve GST activity, thereby reducing oxidative damage and enhancing the antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…As the main member of the second defense line in the antioxidant system, GST can catalyze covalent conjugation reactions between glutathione and toxic electrophilic and hydrophobic substances to produce substances with anti-lipid peroxidation effects. In addition, it can react with some exogenous or endogenous metabolites, such as cholic acid and hormones, which are insoluble in water, to generate some water-soluble compounds, and then they are excreted from the body, thereby protecting brain tissue from antioxidant damage and reducing cellular damage by free radicals and toxic substances [ 39 ]. The results showed that appropriate concentrations of EPA, ALA, or DHA could improve GST activity, thereby reducing oxidative damage and enhancing the antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal domain of ERCC1 interacts with xeroderma pigmentosum group F (XPF), which forms a heterodimeric protein complex. The complex is considered to be the main component of the nucleotide excision repair (NER) pathway ( 15 ). There are several major pathways for repairing DNA damage in human cells, one of which is NER ( 16 ).…”
Section: Introductionmentioning
confidence: 99%